G - C3N4 (2D)/CdS (1D)/rGO (2D) dual-interface nano-composite for excellent and stable visible light photocatalytic hydrogen generation - Tonda, Surendar (International Journal of Hydrogen Energy, 2017)
A 2D/1D/2D dual-interface nano-composite configuration in the form of CdS nanorods sandwiched between g-C3N4 and rGO sheets with intimate interfacial contact is synthesized by a facile wet-chemical method and is shown to exhibit excellent photocatalytic H2 generation under visible-light irradiation. In particular, the optimal g-C3N4/CdS/rGO dual-interface nano-composite shows H2 production rate of ∼4800 μmol h-1 g-1, which is almost 44, 11 and 2.5 times higher than that shown by pure g-C3N4 nanosheets, and the g-C3N4/rGO and g-C3N4/CdS single interface heterostructures, respectively. It is shown that the synergic effects involving the band structure match and close interfacial contact, which can accelerate the separation and transfer of photoinduced charge carriers, and the enhanced visible-light absorption together contribute to the impressive photocatalytic performance and photostability of the g-C3N4/CdS/rGO ternary nano-composite system. Specific advantages of a dual-interface triple-composite system over a single interface case(s) are also brought out.
Keywords: charge transfer; Dual Interface; G - CN; H Generation; Hetero Structure; Nano - Composite

G-C3N4/NiAl-LDH 2D/2D hybrid heterojunction for high-performance photocatalytic reduction ofco2 into renewable fuels - Tonda, Surendar; Kumar, Santosh; Bhardwaj, Monika; Yadav, Poonam; Ogale, Satishchandra (ACS Applied Materials & Interfaces, 2018)
2D/2D interface heterostructures of g-C3N4 and NiAl-LDH are synthesized utilizing strong electrostatic interactions between positively charged 2D NiAl-LDH sheets and negatively charged 2D g-C3N4 nanosheets. This new 2D/2D interface heterojunction showed remarkable performance for photocatalytic CO, reduction to produce renewable fuels such as CO and H-2 under visible-light irradiation, far superior to that of either single phase g-C3N4 or NiAl-LDH nanosheets. The enhancement of photocatalytic activity could be attributed mainly to the excellent interfacial contact at the heterojunction of gC(3)N(4)/NiAl-LDH, which subsequently results in suppressed recombination, and improved transfer and separation of photogenerated charge carriers. In addition, the optimal g-C3N4/NiAl-LDH nanocomposite possessed high photostability after successive experimental runs with no obvious change in the production of CO from CO, reduction. Our findings regarding the design, fabrication and photophysical properties of 2D/2D heterostructure systems may find use in other photocatalytic applications including H-2 production and water purification.